Inovasi K3: Integrasi AI dan IoT untuk Meningkatkan Keselamatan Kerja - Khatami Fahmi Putra, Muhammad; M Zainul, L.; Rusba, Komeyni; Nawawi, Yusuf; Hardiyono, Hardiyono (Dinasti Research, 2024)
This research explores innovations in occupational safety and health (OSH) through AI and IoT integration. The study aims to examine how combining AI and IoT can enhance safety across industries. Using a qualitative analytical descriptive method with an empirical normative approach, data were gathered from journals, documentation, and literature reviews. Results indicate that AI and IoT can identify hazards early, monitor real-time conditions, and provide early warnings. Applications include IoT sensors for detecting hazardous gases and AI for predicting accidents based on historical data. These systems improve incident response and reduce corrective action time, boosting productivity and efficiency. The study recommends broader adoption of AI and IoT in OSH strategies to enhance safety and health in various sectors